PENGUATAN KELEMBAGAAN OMBUDSMAN REPUBLIK INDONESIA DALAM PERSPEKTIF SIYASAH DUSTURIYAH - Nurul Suci Hudayana; Rahmiati (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
The Ombudsman of the Republic of Indonesia is an independent institution that has the authority to supervise the implementation of public services whether administered by the state or private parties. The Ombudsman is authorized to issue product recommendations as an effort to resolve public service violations. However, the recommendations of the Ombudsman of the Republic of Indonesia were not implemented or only partially implemented by the reported and the reported superiors. This study aims to examine the institutional strengthening of the Ombudsman of the Republic of Indonesia with recommendations as a settlement for violations of public service delivery. This research is a juridical research with a conceptual and statutory approach. The data sources used were primary data sources and secondary data, which were collected and then analyzed using analytical descriptive techniques and then concluded. The results of this study concluded that recommendations as a legal product for resolving public service violations were only partially implemented or not even implemented because the recommendations were only considered as suggestions for the reported party and the complainant. In addition, the imposition of sanctions and the execution of administrative sanctions were not carried out by the Ombudsman of the Republic of Indonesia. Furthermore, it is hoped that there will be institutional strengthening of the Ombudsman of the Republic of Indonesia through the revision of the Ombudsman Law of the Republic of Indonesia by changing recommendations into decisions, adding articles related to the form of sanctions that can be imposed on the reported party and/or the reported superiors for the realization of good governance and general welfare.